Role of osteopontin in decidualization and pregnancy success. Issue 5 (May 2018) - Wang, Xiao-Bo; Qi, Qian-Rong; Wu, Kai-Lin; Xie, Qing-Zhen
Abstract : OPN is essential for blastocyst implantation and placentation. Previous study found that miR181a was increased while miR181b was downregulated in endometrium during decidualization. However, the information regarding their effects on decidualization in human endometrium is still limited. Here, we report a novel role of OPN and miR181b in uterine decidualization and pregnancy success in humans. The expression of OPN was high in endometrium in secretory phase and in vitro decidualized hESC, whereas miR181b expression was low in identical conditions. Further analysis confirmed that OPN expression was upregulated by cAMP and C/EBPβ signal pathway, while downregulated by miR181b. Increased OPN expression could promote the expression of decidualization-related and angiogenesis-related genes. Conversely, the processes of decidualization and angiogenesis in hESC were compromised by inhibiting OPN expression in vitro . OPN expression was repressed in implantation failure group when compared with successful pregnancy group in IVF/ICSI-ET cycles. These findings add a new line of evidence supporting the fact that OPN is involved in decidualization and pregnancy success.